FIQH SIYASAH REVIEW OF THE CONSTITUTIONAL COURT'S STANCE REGARDING THE PARLIAMENTARY THRESHOLD - Davil Oswan, Fakhri Muhammad; Edi, Relit Nur; Muhammad, Hasanuddin (Jurnal Al-Dustur, 2025)
The purpose of this research is to analyze fiqh siyasah on the decision of the Constitutional Court Number 116/PUU-XXI/2023 on Parliamentary Threshold. Through a normative juridical approach and fiqh siyasah analysis, this research examines the principles of justice, deliberation and maslahat in accordance with sharia values in decision-making by the panel of judges. This research is normative juridical research, namely research by collecting primary and secondary legal materials that are relevant to research using a conceptual approach, to the decision of the Constitutional Court Number 116/PUU-XXI/2023 both in the study of constitutional law and fiqh siyasah. The results of this study found that the constitutional court emphasized a formal legal approach in decision making so that substantive justice was not achieved. This can be seen that the Constitutional Court continues to impose a parliamentary limit of 4% because it is considered not contrary to the principles of the 1945 Constitution. In the study of fiqh siyasah on the decision of the Constitutional Court Number 116 / PUU-XXI / 2023 concerning Parliamentary Threshold, it shows the lack of substantial judicial ijtihad value. The Court is more inclined to legal formalities than fighting for representative justice which should be the main focus. One of the ijtihad that can be used by the Constitutional Court is ijtihad ta'lili, which is ijtihad based on an analysis of 'illat al-á¸¥ukm (the reason or cause of a legal provision). In this context, the Court should analyze whether the 4% threshold still meets the rationality of justice and democratic effectiveness, or has actually exceeded its original purpose and caused constitutional harm.